Sustainability Index for a Manufacturing Industry: A Case Study of Cement Industry in Nepal - Shakya, Shree Raj; Subedi, Subarna; Bajracharya, Tri Ratna; Shrestha, Shubha Laxmi; Sah, Janu Kumar; Chaulagain, Bibish (Journal of Science and Engineering, 2025)
This paper addresses the gap in applying indicator-based approaches to assess sustainability at the industry level by developing a sustainability index specifically for the manufacturing sector. It incorporates four key factors: material supply, energy supply, socio-economic, and environmental aspects. The cement industry in Nepal, one of the most energy- and emission-intensive sectors, was selected as a case study to test the methodology. The sustainability index was validated by comparing it with trends in energy use, revenue, and production costs. The study revealed that variation in the overall sustainability index was driven by changes across the various indicators representing each sustainability factor. Findings also highlighted that even basic interventions like regular maintenance can lead to notable improvements in sustainability. The proposed approach provides a valuable tool for government bodies and regulatory agencies to assess industry performance over time, particularly when no predefined benchmarks exist. Additionally, the framework supports the setting, monitoring, and evaluation of targets aligned with UN Sustainable Development Goal 12, promoting sustainable production practices. This methodology could further aid in establishing standards and certification systems for sustainable industrial operations.